Beware the Anomalous Portal Vein - Koh, M. K. (Hindawi Publishing Corporation, 1994)
Portal vein thrombosis is an unusual potential complication of liver resection. In our case it was due to ligation of the right branch of the portal vein during right hepatectomy in a patient without portal vein bifurcation. Hepatic angiography can delineate this abnormality and influence the choice of surgical management.